Perancangan Sistem Informasi Point of Sales pada Bengkel Rudal Lubuk Pakam Berbasis Web - Sidabalok, Valentino; Perangin-angin, Resianta; Jamaluddin, Jamaluddin (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
Development of information technology has brought many changes in various The industrial sectors, including the automotive sector. One of the important needs in managing a workshop business is an efficient Point of sales (POS) system to facilitate transaction processes and data management. This research aims to design and implement a web-based Point of sales information system at the Lubuk Pakam Missile Workshop. This system is designed to help manage sales transactions, record spare parts stock, as well as more accurate and integrated financial reporting. This system was built using programming languages such as PHP, HTML, Sublime. With this system, it is hoped that the Lubuk Pakam Missile Workshop can increase operational efficiency, minimize manual recording errors, and speed up the managerial decision making process. The test results show that the system can function well according to user needs, and is able to provide effective solutions in managing workshop operations.